The Formation of Neighborhood Police and Its Impact on the Maintenance of Security and Public Order (Harkamtibmas) at Surabaya Metropolitan Police - Fitrianto, Alif Bagus; Handoko, V. Rudy; Indartuti, Endang (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the implementation of the Neighborhood Police (Polisi RW) policy in efforts to improve public security and order. The research method employed is descriptive analysis with a qualitative approach, involving data collection through interviews, observations, and document review. The findings show that the implementation stages, including planning, socialization, execution, monitoring, evaluation, and development, have had a positive impact, such as increased public awareness, active participation, and more efficient coordination in handling security issues. Another finding reveals that the Prototype model is more relevant than the Incremental model for the Neighborhood Police program, as it allows for rapid feedback and continuous improvement. This study recommends that Regional and City or Regency Police Departments adopt a Prototype-based approach and enhance community involvement in the program to achieve more effective security objectives.